Conservative management of subdural hematoma in idiopathic thrombocytopenic purpura: Report of two cases and review of literature - Sunitha R; Mathew Robert; Thomas Mathew (Annals of Indian Academy of Neurology, 2007)
Intracranial hemorrhage (ICH) is the most serious complication of idiopathic thrombocytopenic purpura (ITP) and is potentially fatal. It is rare, affecting 1% or less of patients and is usually subarachnoid or intracerebral. Isolated subdural hematoma (SDH) is rare and only few cases have been reported. Two cases of acute SDH (ASDH) are reported which resolved with conservative management. One of the patients later developed intracerebral hematoma also. In ITP, contrary to traumatic ASDH, the brain parenchyma is well preserved and hence conservative management may be safe in selected patients. However, only a prospective randomized control study will give the final answer. Both the patients developed the hematoma consequent to low platelet count, which was not detected earlier due to inadequate follow-up. In a developing country, where proper follow-up is often lacking these problems are likely to be more common and are probably underreported. Increased awareness is therefore important to ensure proper follow-up and early intervention.